A Phase II randomized study of galunisertib monotherapy or galunisertib plus lomustine compared with lomustine monotherapy in patients with recurrent glioblastoma - Brandes, Alba; Capper, David; Wick, Wolfgang (Neuro-Oncology, 2016)
AbstractBackground. The combination of galunisertib, a transforming growth factor (TGF)-β receptor (R)1 kinase inhibitor, and lomustine was found to have antit